The Rasch Model: Implementation of Physics Learning Evaluation Instrument Based on Higher Order Thinking Skills - Rika Irmayanti; Muhammad Rusdi; Yusnaidar Yusnaidar (Integrated Science Education Journal, 2023)
Purpose of the study: This research was conducted to analyze the test instruments used to measure students' HOTS abilities on static fluid material at Senior high school 2 Jambi City. Methodology: The evaluation instrument provided was in the form of 20 items of two-tier multiple choice questions related to static fluid material. The Rasch model is used to get fit items. This analysis was carried out with the help of Ministeps software. Respondents in this study were 36 students of class XI MIPA 1 Senior high school 2 Jambi City. Main Findings: From the output of the Ministeps program, the results obtained were 20 questions according to the Rasch model with an average Outfit MNSQ score for person and item respectively 0.94 and 0.94. While the Outfit ZSTD values ​​for persons and items are 0 and -0.1 respectively, while the reliability of the instrument expressed in Cronbach's alpha is 0.79. Novelty/Originality of this study: The evaluation instrument used for physics subjects on static fluid material is fit with the Rasch model. so that the instrument meets the criteria for use.